Branch Retinal Artery Occlusion as a Presenting Feature of Anti-Phospholipid Antibody Syndrome and Homocysteinemia - Richa Agarwal; Vikas Veerwal; Parul Jain; J L Goyal; Neha Jain (Delhi Journal of Ophthalmology)
Retinal artery occlusion (RAO) is an uncommon presentation at a young age. In contrast to retinal artery occlusion in the elderly, where the most common mechanism of occlusion involves embolic disease from the carotid artery, RAO in young adults occur secondary to a diverse group of pathologic conditions, like hypercoagulable states leading to thrombosis, antiphospholipid syndrome (APS), elevated homocysteine levels. We report a unique case of a young female who presented with decreased vision in her right eye due to a branch RAO. Thorough systemic evaluation led to a diagnosis of APS along with presence of hyperhomocysteinemia and Rheumatic Heart Disease. Patient was advised warfarin therapy along with vitamin supplementation to reduce the risk of further thrombotic events. By means of this report, we would like to highlight that the high prevalence of underlying systemic disease in young patients with RAO necessitates a thorough, aggressive examination to rule out potential life-threatening embolic and hypercoagulable conditions.